Cyclical systemic risk and downside risks to bank profitability - Jan Hannes Lang; Marco Forletta (European Central Bank (ECB), 2020)
This paper studies the impact of cyclical systemic risk on future bank profitability for a large representative panel of EU banks between 2005 and 2017. Using linear local projections we show that high current levels of cyclical systemic risk predict large drops in the average bank-level return on assets (ROA) with a lead time of 3-5 years. Based on quantile local projections we further show that the negative impact of cyclical systemic risk on the left tail of the future bank-level ROA distribution is an order of magnitude larger than on the median. Given the tight link between negative profits and reductions in bank capital, our method can be used to quantify the level of "Bank capital-at-risk" for a given banking system, akin to the concept of "Growth-at-risk". We illustrate how the method can inform the calibration of countercyclical macroprudential policy instruments.
Keywords: G01; G17; C22; C54; G21; 330; Local projections; quantile regressions; systemic risk; Growth-at-risk; bank profitability